Commodification, Spatialization, and Structuration in Collaboration Between Local Media and Local Government in West Java - Ruswandi, Awang (UI Scholars Hub, 2025)
In the era of local government autonomy and decentralization, numerous collaborations have emerged between local governments and local media, particularly in reporting government activities. Utilizing Vincent Mosco's political economy of communication framework, this study aims to elucidate the power relations manifested through commodification, specialization, and structuration between local media and government. This qualitative case study gathers data through in-depth interviews. Findings reveal that local government media cooperation funds serve as a mechanism to secure special coverage spaces with positive content about governmental activities, not in the form of advertising or advertorial, but in the form of news. While financially beneficial for both entities, these collaborations compromise journalistic integrity. Local media face censorship, framing, reprimands, and potential contract terminations, effectively granting local governments control over editorial processes and content. Consequently, local media are hindered in their ability to critically oversee governmental actions, posing significant challenges to media freedom—a fundamental pillar of democracy.